COL1A2 is a TBX3 target that mediates its impact on fibrosarcoma and chondrosarcoma cell migration. (10th September 2019) - Omar, Rehana; Cooper, Aretha; Maranyane, Hapiloe Mabaruti; Zerbini, Luiz; Prince, Sharon
Abstract: The developmentally important T-box transcription factor TBX3, is overexpressed in several cancers and contributes to tumorigenesis as either a tumour promoter or tumour suppressor. For example, TBX3 promotes cell proliferation, migration and invasion of chondrosarcoma cells but inhibits these processes in fibrosarcoma cells. This suggests that the cellular context influences TBX3 oncogenic functions, but the mechanism(s) involved has not been elucidated. COL1A2 encodes type I collagen and, like TBX3, plays important roles during embryogenesis and can act as either oncogene or tumour suppressor. Here we explore the possibility that COL1A2 may be a TBX3 target gene responsible for mediating its opposing oncogenic roles in chondrosarcoma and fibrosarcoma cells. Results from qRT-PCR, western blotting, luciferase reporter and chromatin immunoprecipitation assays show that TBX3 binds and activates the COL1A2 promoter. Furthermore, we show that TBX3 levels are regulated by AKT1 and that pseudo-phosphorylation of TBX3 at an AKT consensus serine site, enhances its ability to activate COL1A2. Importantly, we demonstrate that COL1A2 mediates the pro- and anti-migratory effects of TBX3 in chondrosarcoma and fibrosarcoma cells respectively. Our data reveal that the AKT1/TBX3/COL1A2 axis plays an important role in sarcomagenesis. Graphical abstract: Image 1 Highlights: TBX3 directly activates C OL1A2 in fibrosarcoma and chondrosarcoma. AKT1 positively regulates TBX3 levels in fibrosarcoma and chondrosarcoma. Pseudo-phosphorylation of TBX3 at an AKT motif enhances its activation of COL1A2 . COL1A2 mediates the anti- and pro-migratory roles of TBX3. The AKT1/TBX3/COL1A2 axis regulates fibrosarcoma and chondrosarcoma migration.